The psychology book (Big ideas simply explained, 2011)
Clearly explaining more than 100 groundbreaking ideas in the field, The Psychology Book uses accessible text and easy-to-follow graphics and illustrations to explain the complex theoretical and experimental foundations of psychology. From its philosophical roots through behaviorism, psychotherapy, and developmental psychology, The Psychology Book looks at all the greats from Pavlov and Skinner to Freud and Jung, and is an essential reference for students and anyone with an interest in how the mind works